Isolation And Characterisation Of Vasicine From In Vitro Cultures Of Justicia Adhatoda L - RASHMI P A; RESHMA JOHN; LINU MATHEW (International Journal of Pharma and Bio Sciences, 2012)
Justicia adhatoda L. which belongs to the family of Acanthaceae contains alkaloids like vasicine, vasicinone and deoxyvasicine. These alkaloids give the plant its expectorant activity, antispasmodic, antiseptic and antihelmintic properties. Hence, in the present investigation attempts were made to isolate and characterise alkaloids from callus and suspension cultures of J. adhatoda. Alkaloids were extracted with methanol, quantified and identified by colour reactions, Thin layer chromatograms (TLC), High performance liquid chromatogram (HPLC) and Fourier transform infrared spectroscopy (FT-IR) using vasicine as standard.